Identification of an Autoantibody Against ErbB-3-Binding Protein-1 in the Sera of Patients With Chronic Hepatitis B Virus Infection - Jiang, Li; Niu, Wei; Zheng, Qian; Meng, Gang; Chen, Xiaoling; Zhang, Mengjun; Deng, Guohong; Mao, Qing; Wang, Li (Frontiers in Immunology, 2021)
Abstract Background: Studies have shown that autoimmune response contributes to chronic hepatitis B (CHB) development. Aim: This study aimed to identify autoantibodies in the sera of patients with CHB and to investigate the association of autoimmune response with disease severity in CHB. Methods: Proteins from human liver carcinoma cell line HepG2 were separated by two-dimensional electrophoresis. The candidate autoantigens were recognized by serum autoantibodies from Chinese CHB patients. Immunohistochemical staining was performed to determine the hepatic expression of the autoantigen in CHB patients with different inflammatory grades. Enzyme-linked immunosorbent assay (ELISA) was conducted to measure the prevalence and the levels of serum autoantibody in CHB patients with different disease severity. Flow cytometry analysis was carried out to assess the autoreactive T cell response in the peripheral circulation of CHB patients. Results: ErbB-3-binding protein-1 (EBP-1) was identified as an autoantigen of serum autoantibodies in CBP patients. EBP-1 protein expression was upregulated in the liver of CHB patients with high-grade hepatic inflammation. The prevalence and levels of serum anti-EBP1 IgG were significantly increased in CHB patients with severe diseases compared with those with mild or moderate diseases, but none was detectable in the healthy controls. EBP-1 peptides induced proinflammatory cytokine expression in CD4+ T cells from CHB patients. Conclusion: Our results demonstrate the presence of an autoantibody against EBP-1 in the sera as well as EBP-1-reactive T cells in the peripheral blood of CHB patient. EBP-1-induced autoimmune response is positively associated with the disease severity, suggesting that EBP-1-induced autoimmune response possibly contributes to progressive liver failure.